2018
DOI: 10.17218/hititsosbil.461486
|View full text |Cite
|
Sign up to set email alerts
|

Futbol Hakemleri̇ni̇n Kendi̇ni̇ Sabotaj Düzeyleri̇

Abstract: Bu çalışmanın amacı Çorum ilinde faal olarak görev yapan futbol hakemlerinin kendini sabotaj düzeylerinin belirlenmesidir. Çalışmada katılımcıların kendini sabotaj düzeylerinin, yaş, cinsiyet, hakem yaşı, eğitim düzeyi, gelir düzeyi gibi değişkenler açısından da incelenmesi amaçlanmıştır. Çalışmanın araştırma grubunu Çorum ilinde faal olarak görev yapan futbol hakemleri (N= 49) oluşturmaktadır. Elde edilen veriler Jones ve Rhodewalt tarafından geliştirilip, Akın tarafından Türkçe' ye uyarlanmış olan 25 soruluk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…When the findings related to demographic variables are examined, our results align with previous findings in which SE, SC, and SH levels do not differ according to gender (Doğan, Totan, & Sapmaz, 2009;Kamuk, Evli, & Tecimer, 2018;Zuckerman & Tsai, 2005). A possible explanation for the indifferences according to gender may be the diminishing gap in performance expected from men and women in today's academic settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When the findings related to demographic variables are examined, our results align with previous findings in which SE, SC, and SH levels do not differ according to gender (Doğan, Totan, & Sapmaz, 2009;Kamuk, Evli, & Tecimer, 2018;Zuckerman & Tsai, 2005). A possible explanation for the indifferences according to gender may be the diminishing gap in performance expected from men and women in today's academic settings.…”
Section: Discussionsupporting
confidence: 88%
“…Yüksek öz şefkat düzeyine sahip olmak, hata yapmayı bütün insanlığın ortak bir deneyimi olarak görmeyi beraberinde getirmektedir. Böyle bir bakış açısı bireyin hatalarının üzerini örtme işlevi taşıyan bahaneler üretmesini gereksiz kılabilmektedir.Bulgular cinsiyet açısından incelendiğinde ise literatürde bulgularımızı destekler şekilde benlik saygısı, öz şefkat ve kendini sabotaj düzeylerinin cinsiyete göre farklılık göstermediği çalışmaların mevcut olduğu görülmektedir (örn.,Doğan, Totan ve Sapmaz, 2009;Kamuk, Evli ve Tecimer, 2018; Zuckerman ve Tsai, 2005). Güleç ve Özbek Ayaz'a (2017) göre benlik saygısındaki farklılık cinsiyetten ziyade aile, çevre ve sosyokültürel faktörlerle ilgili olabilir.…”
unclassified
“…Zuckerman and Tsai (2005) and Büyükgöze and Gün's (2015) attempts proved against significant differences in participants' self-handicapping levels by gender. Moreover, Kamuk, Evli and Tecimer (2018) revealed no significant difference regarding male and female football referees' self-handicapping levels. This study detected no significant difference in sports management students' self-handicapping levels by gender.…”
Section: Discussionmentioning
confidence: 76%
“…Topal, Yalnızoğlu Çaka and Çınar (2018) found that younger nursing students had higher levels of self-handicapping. Kamuk et al (2018) determined that football referees' self-handicapping levels exhibit significant difference by age. Zafer (2016) determined that participants' self-handicapping levels did not show significant differences by age in firefighters aged between 20 and 40.…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study on the referees were found. The study was conducted by Kamuk et al (2018) to determine the self-handicapping levels of football referees. According to the results of that study, the average of football referees' self-handicapping score was found to be 50.39±12.61 and the median value was 51.…”
Section: Turkish Studies -Social Sciencesmentioning
confidence: 99%